A non-synonymous SNP with the allele frequency correlated with the altitude may contribute to the hypoxia adaptation of Tibetan chicken. - Sichen Li; Diyan Li; Xiaoling Zhao; Yan Wang; Huadong Yin; Lanyun Zhou; Chengling Zhong; Qing Zhu (PLoS ONE, 2017)
The hypoxia adaptation to high altitudes is of considerable interest in the biological sciences. As a breed with adaptability to highland environments, the Tibetan chicken (Gallus gallus domestics), provides a biological model to search for genetic differences between high and lowland chickens. To address mechanisms of hypoxia adaptability at high altitudes for the Tibetan chicken, we focused on the Endothelial PAS domain protein 1 (EPAS1), a key regulatory factor in hypoxia responses. Detected were polymorphisms of EPAS1 exons in 157 Tibetan chickens from 8 populations and 139 lowland chickens from 7 breeds. We then designed 15 pairs of primers to amplify exon sequences by Sanger sequencing methods. Six single nucleotide polymorphisms (SNPs) were detected, including 2 missense mutations (SNP3 rs316126786 and SNP5 rs740389732) and 4 synonymous mutations (SNP1 rs315040213, SNP4 rs739281102, SNP6 rs739010166, and SNP2 rs14330062). There were negative correlations between altitude and mutant allele frequencies for both SNP6 (rs739010166, r = 0.758, p<0.001) and SNP3 (rs316126786, r = 0.844, P<0.001). We also aligned the EPAS1 protein with ortholog proteins from diverse vertebrates and focused that SNP3 (Y333C) was a conserved site among species. Also, SNP3 (Y333C) occurred in a well-defined protein domain Per-AhR-Arnt-Sim (PAS domain). These results imply that SNP3 (Y333C) is the most likely casual mutation for the high-altitude adaption in Tibetan chicken. These variations of EPAS1 provide new insights into the gene's function.